Transport of Aflatoxin M1 in Human Intestinal Caco-2/TC7 Cells - Caloni, Francesca (Frontiers in Pharmacology, 2012)
Aflatoxin M1 (AFM1) is a hydroxylated metabolite of aflatoxin B1 (AFB1). After it is formed, it is secreted in the milk of mammals. Despite the potential risk of human exposure to AFM1, data reported in literature on the metabolism, toxicity and bioavailability of this molecule are limited and out of date. The aim of the present research was to study the absorption profile of AFM1 and possible damage to tight junctions of the intestinal Caco-2/TC7 clone grown on microporous filter supports. These inserts allowed for the separation of the apical and basolateral compartments which correspond to the in vivo lumen and the interstitial space/vascular systems of intestinal mucosa respectively. In this study, the Caco-2/TC7 cells were treated with different AFM1 concentrations (10-10,000 ng/kg) for short (40 minutes) and long periods of time (48 hours). The AFM1 influx/efflux transport and effects on tight junctions were evaluated by measuring trans-epithelial electrical resistance and observing tight junction protein (Zonula occludens-1 and occludin) localization. The results showed that: i) when introduced to the apical and basolateral compartments, AFM1 was poorly absorbed by the Caco-2/TC7 cells but its transport across the cell monolayer occurred very quickly (Papp value of 105.10 ± 7.98 cm/s x 10-6). ii) The integrity of tight junctions was not permanently compromised after exposure to the mycotoxin. Viability impairment or barrier damage did not occur either. The present results contribute to the evaluation of human risk exposure to AFM1, although the AFM1 transport mechanism need to be clarified.